Archiving traditional houses through digital social mapping: an innovation approach for living heritage conservation in Java - Suprapti, Atiek; Sejati, Anang Wahyu; Pandelaki, Edward Endrianto; Sardjono, Agung Budi (Journal of Architecture and Urbanism, 2022)
Indonesia has various types of traditional houses, one of which is the most unique architectural work that is the Joglo Pencu (JP) house. It also has a meaning by reason of a symbol which defines as the development of culture and identity. The role of community in the conservation of cultural heritage buildings is very important. However, due to the pressure of urbanization, many heritage buildings transitioned into modern houses. The study area is the historic area of Kudus city, which previously had a significant influence on Islamic architecture due to its residential model. This study aims to provide a social mapping using GIS and primary survey involves community participation of living heritage. As a result, IT becomes the bridge between conservation needs and management patterns of structured organizations that connects all stakeholders. By innovation of digital social mapping, it will be a bridge for the participation of living heritage community with a more transparent and accountable conservation management. In this case, it is shown that Kudus has experienced cultural shifting and transition in traditional houses. The architectural design of the houses that was initially in JP has begun to disappear. The role of the community in social mapping is very decisive in providing data accuracy. Lacking in preservation and maintenance are the main factors, especially the minimum effort from local government. Therefore, active cooperation between cultural communities, communities, and the government is needed to be able to keep the existence of JP intact as a historical heritage building.